Relationship between audit committee characteristics and company performance: evidence from Malaysian companies / Nur Baiti Shafee - Shafee, Nur Baiti (2011)
The existence of an audit committee in a company has become an issue on whether their presence can enhance the performance of the company, especially when event of corporate failures happened to the companies that have established audit committee in their organizations. This paper seeks to investigate the relationship between the audit committee characteristics and corporate performance, where performance is proxied by the Returned on Assets. The four audit committee characteristics examined in this study are size, independence, activity and the financial literacy in audit committee. The data are gathered from the analysis of companies' annual report for a sample of 169 listed at Bursa Malaysia. The data set is obtained from the annual reports for the year 2009. Multiple regression models are applied to test the significance of audit committee characteristics and firm performance. The result shows that both activity and financial literacy have a relationship with the company's performance. It means that firms having good audit committee perform well compared to the firms having no or less audit committee.